Novel chyme reinfusion device for gastrointestinal fistulas and stomas: feasibility study. Issue 9 (18th April 2020) - Sharma, P; Davidson, R; Davidson, J; Keane, C; Liu, C; Ritchie, S R; Chu, K; Sutherland, G; Bissett, I P; O'Grady, G
Abstract: Background: High-output enterostomies and enteroatmospheric fistulas are common causes of intestinal failure, and may necessitate parenteral nutrition and prolonged hospital stay. Reinfusing lost chyme into the distal gut is known to be beneficial, but implementation has been limited because manual reinfusion is unpleasant and labour-intensive, and no devices are available. A new device is presented for reinfusing chyme easily and efficiently, with first-in-human data. Methods: The device comprises a compact centrifugal pump that fits inside a standard stoma appliance. The pump is connected to an intestinal feeding tube inserted into the distal intestinal limb. The pump is activated across the appliance by magnetic coupling to a hand-held driver unit, effecting intermittent bolus reinfusion while avoiding effluent contact. Safety, technical and clinical factors were evaluated. Results: Following microbiological safety testing, the device was evaluated in ten patients (median duration of installation 39·5 days; total 740 days). Indications included remediation of high-output losses (8 patients), dependency on parenteral nutrition (5), and gut rehabilitation before surgery (10). Reinfusion was well tolerated with use of regular boluses of approximately 200 ml, and no device-related serious adverse events occurred. Clinical benefits included resumption of oral diet, cessation of parenteral nutrition (4 of 5 patients), correction of electrolytes and liver enzymes, and hospital discharge (6 of 10). Of seven patients with intestinal continuity restored, one experienced postoperative ileus. Conclusion: A novel chyme reinfusion device was developed and found to be safe, demonstrating potential benefits in remediating high-output losses, improving fluid and electrolyte balance, weaning off parenteral nutrition and improving surgical recovery. Pivotal trials and regulatory approvals are now in process. Graphical Abstract: A novel chyme recycling device for high-output enterostomies and enteroatmospheric fistulas. Benefits in high output gastrointestinal loss